Practical design and implementation of an autonomous surface vessel prototype: Navigation and control. (8th May 2020) - Tang, Xinhua; Pei, Zhonghai; Yin, Shiming; Li, Cong; Wang, Peng; Wang, Yu; Wu, Zhiqiang
As the development of multidisciplinary techniques and ever-growing demands, autonomous system has been widely investigated in a variety of fields. In recent two decades, autonomous surface vessels have gained increasing attention from both industry and research communities, previous related work mainly focuses on the design of maneuver controllers, most algorithms are under some specific assumptions and always involve too many parameters that need to be tuned, leading to the lack of practical application or validation in real autonomous surface vessel platform. To tackle the issues, an integrated autonomous surface vessel prototype is designed and implemented, both navigation and maneuver control subsystems are improved, especially in terms of autonomous control, a simple geometrical model and constrained pure pursuit algorithm is firstly tried in autonomous surface vessel, the results show that the proposed system can achieve the path tracking with the error smaller than 40 cm, and even given a complicated waypoint mission, it can still maintain the accuracy of path tracking, demonstrating the stability and validity of the autonomous surface vessel prototype.